4‐Methylumbelliferone promotes the migration and odontogenetic differentiation of human dental pulp stem cells exposed to lipopolysaccharide in vitro. (13th April 2021) - Chen, Weiting; Guan, Yun; Xu, Fangfang; Jiang, Beizhan
Abstract: Hyaluronic acid (HA), a major component of the extracellular matrix, is essential to inflammatory regulation. 4‐Methylumbelliferone (4‐mu), as the specific inhibitor of HA synthesis, is an anti‐inflammatory in multiple systems. However, there have been no studies, to our knowledge, regarding 4‐mu treatment in pulp inflammation. Therefore, the purpose of this study was to investigate the effects of 4‐mu on biological behaviors in human dental pulp stem cells (hDPSCs) exposed to lipopolysaccharide (LPS) in vitro. hDPSCs were exposed to LPS to construct the inflammation model in vitro. Immunocytochemistry, quantitative polymerase chain reaction, western blotting, Cell Counting Kit‐8, scratch/Transwell assay, and alizarin red staining/alkaline phosphatase staining were selected to explore the effect of 4‐mu on the expression of inflammatory factors, cell proliferation, cell migration, and the odontogenic differentiation ability of hDPSCs. LPS stimulated hDPSCs to highly express the related inflammatory factors and CD44 (the major HA receptor), which were all inhibited by 0.1 mM of 4‐mu. In addition, the cell proliferation ability of hDPSCs was suppressed by 4‐mu, while cell migration and odontogenic differentiation abilities were significantly improved under inflammation. In conclusion, 4‐mu suppressed inflammatory cytokines in inflamed hDPSCs and had a positive effect on the migration and odontogenic differentiation of hDPSCs.